2019
DOI: 10.3389/fimmu.2019.01402
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Glucose Metabolism to Enhance Immunotherapy: Emerging Evidence on Intermittent Fasting and Calorie Restriction Mimetics

Abstract: There is growing interest in harnessing lifestyle and pharmaceutical interventions to boost immune function, reduce tumor growth, and improve cancer treatment efficacy while reducing treatment toxicity. Interventions targeting glucose metabolism are particularly promising, as they have the potential to directly inhibit tumor cell proliferation. However, because anti-tumor immune effector cells also rely on glycolysis to sustain their clonal expansion and function, it remains unclear whether glucose-modulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 78 publications
0
48
0
1
Order By: Relevance
“…As we will discuss throughout this review, targeting glucose metabolism concomitantly provides an opportunity to improve the longevity of the anti-tumor T cell response and to contrast tumor growth, thus representing a therapeutic option to be contemplated in immunotherapeutic strategies. Nonetheless, considering that T cells rely on glucose metabolism for their activation, glucose-modulating therapies may concomitantly support and hamper anti-tumor immunity [ 9 ], suggesting that predictive biomarker-based approaches should be implemented. Moreover, potential side effects, off-target effects, and the complexity of the whole-body metabolism can interfere with the effectiveness of a metabolic manipulation in cancer settings.…”
Section: Introductionmentioning
confidence: 99%
“…As we will discuss throughout this review, targeting glucose metabolism concomitantly provides an opportunity to improve the longevity of the anti-tumor T cell response and to contrast tumor growth, thus representing a therapeutic option to be contemplated in immunotherapeutic strategies. Nonetheless, considering that T cells rely on glucose metabolism for their activation, glucose-modulating therapies may concomitantly support and hamper anti-tumor immunity [ 9 ], suggesting that predictive biomarker-based approaches should be implemented. Moreover, potential side effects, off-target effects, and the complexity of the whole-body metabolism can interfere with the effectiveness of a metabolic manipulation in cancer settings.…”
Section: Introductionmentioning
confidence: 99%
“…These changes lead to functional programming in TAMs, including the production of cytokines and angiogenetic factors, and result in tumor progression and metastasis. Consumption of the energy sources (e.g., glucose) can support tumor growth, and the glucose metabolism product lactate is an important immunosuppressive metabolite in the tumor microenvironment and a driving factor for TAM-2 polarization [69]. In addition, the hypoxia and low pH of the tumor microenvironment can hinder antitumor immune responses of tumor-infiltrating T cells by limiting nutrient and energy consumption [70].…”
Section: Tumor Microenvironment-targeting Nanomedicinementioning
confidence: 99%
“…Consequently, the identification of novel molecular and genetic biomarkers for diagnosis, prognostic estimation, and therapeutic targets for HER2+ breast cancer patients is necessary. Recent studies have revealed that a series of metabolic alterations, especially in glucose metabolism, allow cancer cells to acquire more nutrients and energy to promote rapid proliferation and metastasis [37,38]. Previous studies have also reported that SGLT1 is highly expressed in various malignant tumor cells of epithelial origin.…”
Section: Disease Markersmentioning
confidence: 99%